AĞ TOPLUMUNDA ÖRGÜTLENME: FACEBOOK’TA ÇEVRİMİÇİ TEKEL EYLEMİ - Göker, Göksel; Doğan, Adem (Balıkesir Üniversitesi, 2011)
Problem: Günümüzde, modern toplumları açıklamakta kullanılan kavramların başında “Ağ Toplumu” gelmektedir. Özellikle internet teknolojilerinin gelişmesiyle birlikte dünya üzerinde birbirine internet ağı ile bağlanan insanların iletişim ve etkileşim süreçleri bu kavramın yaygın kullanımında etkili olmuştur. Bireylerin siyasi, ekonomik, kültürel ve eğlence amaçlı bir araya gelmelerini sağlayan ağ toplumunun, kişilerin belirli toplumsal olay ve sorunlar etrafında örgütlenmelerini de kolaylaştırdığı görülmektedir. İnternet tabanlı iletişim ağlarının toplumsal olay ve sorunlar karşısında örgütlenme sürecindeki etkisi araştırmanın temel problematiğini oluşturmaktadır. Araştırmanın Amacı: Araştırmanın temel amacı Tekel işçilerine destek olmak amacıyla Facebook sosyal paylaşım sitesinde örgütlenen eyleme destek grubu üyelerinin, gruba katılma amaçları ve gruba ilişkin tutumlarının belirlenmesidir. Ayrıca eyleme destek amacıyla kurulan grup içerisinde yapılan paylaşımlar ve grup üyelerinin grup içerisindeki etkinlik düzeyinin saptanması araştırmanın diğer bazı amaçlarıdır. çoğunluğunun grup içerisindeki paylaşım, katkı ve değerlendirme gibi aktivitelerde aktif rol almadığı ve grup üyelerinin çoğunluğunun grubun etkinliğine ilişkin olumlu kanaatlere sahip olduğu tespit edilmiştir

Problem: Today “Network Society” is the main concept used to define the modern societies. By the development in internet technologies, the communication and interactivity of the people connecting each other on internet had led the usage of this concept widespread. It is also observed in the network society which gathers the individuals for the purpose of political, economic, cultural and entertainment reasons, that this situation eases them to be organized around certain social events and problems. The basic problematic of the research is the effect of the internet based communication networks to the organizing process due to the social events and problems.Aim of the Research: The main aim of the research is to determine the intentions and the attitudes of the members who are organized in the social network Facebook to support the Tekel workers. Detecting the shares done in the protest supporting group and the activity level of the members in the group are some other purposes of the research.Method: The field study method is used in the research and to collect data, survey analysis technique is applied. While the group members are the population of the survey, the sample is the 477 group member who has filled the questionary published on the main page of the group. Findings: The findings derived from the research are transferred into the SPSS 16 packet program then the frequency and percentage analysis are done. Besides, to designate if there is a correlation between the variables or not, the Chi-Square independency test is applied. Conclusions and Discussion: According to the findings derived from the sample group, it is determined that there are members in the group from any age, profession and educational status, a high majority of the sample did not joined the protest actually, mostly the friend recommends were efficient in being aware of the group, most of the group members did not actually take a role in sharing, contributing and evaluating activities in the group and finally most of the group members had positive opinions about the efficiency of the group
Organization on Network Society: Online Tekel Protest on Facebook